Skrining Fitokimia Dan Uji Aktivitas Ekstrak Etanol Batang Jarak Pagar (Jatropha curcas L.) Sebagai Antibakteri Staphylococcus aureus - Novia, Devi; Herlina; Luki Dharmayanty (SINTA Journal (Science, Technology, and Agricultural), 2025)
Traditionally, the castor plant (Jatropha curcas L.) has been used by the community as a traditional medicine, particularly its leaves. This plant is commonly used to treat various health complaints such as fever, skin disorders, toothaches, canker sores, wounds, rheumatism, coughs, bloating, and other ailments. Castor leaf extract is known to contain secondary metabolite compounds, including alkaloids, flavonoids, saponins, tannins, and polyphenols, while the compounds in the stem have not been determined. This study was conducted to screen for secondary metabolites and assess how much the stem of Jatropha curcas L. can inhibit the growth of Staphylococcus aureus bacteria. The method used to test the antibacterial activity of the ethanol extract of castor stems was the disk diffusion method. The results showed that the ethanol extract of castor stems (Jatropha curcas L.) contains secondary metabolites and has the ability to inhibit the growth of Staphylococcus aureus bacteria. The most effective concentration was found at 75%, with an average inhibition zone diameter of 19.7 mm.